638 The Implication of Telephone Consultations During COVID-19 Pandemic on Informed Consent. (12th October 2021) - Ayoub, N; Gareb, F; Akhtar, M
Abstract: Aim: Is to find whether telephone consultations have affected patient's comprehension of the proposed surgical management and possible risks until the day of surgery and accordingly ability for informed consent. Method: This study included a sample of patients admitted to QEQM hospital for elective day case surgery during November 2020 and had only telephone consultation when referred for surgery. A feedback survey assessing quality of information given to patients before and on day of surgery was filled by the patients after the procedure. Results: The sample included 40 patients undergoing different procedures [cholecystectomy (25), inguinal hernia repair (25), rectal examination under anaesthesia (5), ventral hernia repair (2), incisional hernia (2), inguinal lymph node biopsy (1)]. It was found that 27.5% of patients didn't have thorough explanation of possible risks and no explanation about postoperative care in 35%.20% were not provided a leaflet about procedure, 57.5% had concerns before surgery and 75% of patients wished for a leaflet with illustrative diagrams, explanation of risks with their management to be able to take the right decision and majority of these patients were from cholecystectomy subgroup. Conclusions: The lack of face-face appointment affected greatly the informed consent process resulting in patient dissatisfaction which raised the need for new leaflets containing diagrammatic explanation of procedures and possible risks with their management to ensure fulfilment of autonomy principle.